RESPON PERTUMBUHAN DAN HASIL BUNCIS (Phaseolus vulgaris L.) KULTIVAR LEBAT–3 AKIBAT TAKARAN PUPUK ANORGANIK DAN JARAK TANAM - Yudi Yusdian; Meki Mulyadi (Paspalum: Jurnal Ilmiah Pertanian, 2017)
The experiment was conducted at Village Margamulya, Pangalengan, Bandung regency, West java. Trial sites located at an altitude of 1,200 meters above sea level, with an average rainfall of 2.186,10 mm/year, precipitation type C3 acording toOldeman (1975). The research was conducted to find the interaction of various doses of NPK (16:16:16) fertilizer and plant spacing on growth and yield of beans (Phaseolus vulgaris L.) Lebat-3 cultivars. The experiment using an experimental method Randomized Block Design consist of two factors: dose of NPK (16:16:16)  (p) of 3 levels  p1 = 250 kg/ha, p2 = 350 kg/ha, and p3 = 450 kg/ha and plant spacing (t) of 3 levels    t1 = 40 x 60 cm, t2 = 40 x 70 cm, t3 = 40 x 70 cm, repeated three times, there ware 27 experimental plots. The results showed there way an interaction on the parameters of weight pods per plot which produces weight 5.08 kg / plot equivalent to 12.7 ton/ha. Dosage of fertilizer NPK (16:16:16) 450 Kg/ha gave better  results on showed that on plant height, weight of pods per plant.